Design, synthesis, and α‐glucosidase‐inhibitory activity of phenoxy‐biscoumarin–N‐phenylacetamide hybrids. Issue 12 (31st August 2021) - Ansari, Samira; Azizian, Homa; Pedrood, Keyvan; Yavari, Ali; Mojtabavi, Somayeh; Faramarzi, Mohammad A.; Golshani, Shiva; Hosseini, Samanesadat; Biglar, Mahmood; Larijani, Bagher; Rastegar, Hossein; Hamedifar, Haleh; et al.
Abstract: Thirteen new phenoxy‐biscoumarin– N ‐phenylacetamide derivatives (7a –m ) were designed based on a molecular hybridization approach as new α‐glucosidase inhibitors. These compounds were synthesized with high yields and evaluated in vitro for their inhibitory activity against yeast α‐glucosidase. The obtained results revealed that a significant proportion of the synthesized compounds showed considerable α‐glucosidase‐inhibitory activity in comparison to acarbose as a positive control. Representatively, 2‐(4‐(bis(4‐hydroxy‐2‐oxo‐2 H ‐chromen‐3‐yl)methyl)phenoxy)‐ N ‐(4‐bromophenyl)acetamide (7f ), with IC50  = 41.73 ± 0.38 µM against α‐glucosidase, was around 18 times more potent than acarbose (IC50  = 750.0 ± 10.0 µM). This compound was a competitive α‐glucosidase inhibitor. Molecular modeling and dynamic simulation of these compounds confirmed the obtained results through in vitro experiments. Prediction of the druglikeness/ADME/toxicity of the compound 7f and comparison with the standard drug acarbose showed that the new compound 7f was probably better than the standard drug in terms of toxicity. Abstract : A series of new phenoxy‐biscoumarin– N ‐phenylacetamide derivatives (7a –m ) were designed as new α‐glucosidase inhibitors, based on a molecular hybridization approach. Many of the synthesized compounds show considerable α‐glucosidase‐inhibitory activity in comparison to the standard drug acarbose. The new compound 7f shows also better results in terms of toxicity than acarbose.